2022
DOI: 10.3389/fenrg.2021.804706
|View full text |Cite
|
Sign up to set email alerts
|

Towards Achieving Environmental Sustainability: The Role of Nuclear Energy, Renewable Energy, and ICT in the Top-Five Carbon Emitting Countries

Abstract: In the era of globalization, the incidence of global warming emerges from the issue of climate change, which attracts the attention of several scholars to attain sustainability with respect to ensuring sufficient energy access and diminishing environmental adversities. However, in view of these circumstances, this study examines the heterogenous impacts of nuclear energy, renewable energy, and information and communication technologies (ICTs) on pollution emissions reduction for the top-five emitter countries,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 70 publications
8
16
0
1
Order By: Relevance
“…This indicates that China's efforts to stimulate its economy through techniques that aren't environmentally friendly are counterproductive to the country's efforts to achieve carbon neutrality. This result is consistent with the claims made by Liu et al (2017b), Azam et al (2022), , , , Raihan and Tuspekova (2022b), Raihan and Tuspekova (2022e), Raihan and Tuspekova (2022f), Raihan and Voumik (2022), Raihan and Tuspekova (2022g), , Tuspekova (2022i), andZafar et al (2022) in which the authors argued that economic development degrades environmental quality. The availability of affordable, reliable energy sources is also crucial to the success of any economy (Raihan & Tuspekova, 2022j).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This indicates that China's efforts to stimulate its economy through techniques that aren't environmentally friendly are counterproductive to the country's efforts to achieve carbon neutrality. This result is consistent with the claims made by Liu et al (2017b), Azam et al (2022), , , , Raihan and Tuspekova (2022b), Raihan and Tuspekova (2022e), Raihan and Tuspekova (2022f), Raihan and Voumik (2022), Raihan and Tuspekova (2022g), , Tuspekova (2022i), andZafar et al (2022) in which the authors argued that economic development degrades environmental quality. The availability of affordable, reliable energy sources is also crucial to the success of any economy (Raihan & Tuspekova, 2022j).…”
Section: Resultssupporting
confidence: 92%
“…For instance, Raihan and Tuspekova (2022a) reported a positive relationship between economic growth and CO2 emissions while a negative relationship between renewable energy use and CO2 emissions in Peru utilizing the data over 1990-2018. By using an advanced panel quantile regression model, Azam et al (2022) reported a positive relationship between economic growth and CO2 emissions, and a negative relationship between renewable energy and CO2 emissions in the top-five emitter countries, covering the data from the period from 1995 to 2017. By utilizing data from 1990 to 2019, reported a positive relationship between economic growth and CO2 emissions, and a negative relationship between renewable energy and CO2 emissions in Argentina.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similar findings were reported by (Iwata, et al, 2012) for 11 OECD countries, in whose case a positive impact of nuclear power on carbon dioxide emissions was found only in Finland, Japan, Korea and Spain (Hassan, et al, 2020). studied BRICS countries between 1993 and 2017 and found that nuclear energy, although effective for emissions reduction, is suboptimal to renewable energy in fostering declines in pollution (Azam, et al, 2022). confirm the insignificant contribution that nuclear energy makes to mitigating environmental pollution for the top five polluting countries (China, United States, India, Japan, and South Korea), albeit accompanied by a strong positive impact of renewable energy consumption on emissions.…”
Section: Pollution and Energy MIXsupporting
confidence: 74%
“…In addition, many countries in Europe and around the world are rebuilding their energy systems under the influence of the increasingly stronger impact of globalization processes, which include shaping national energy strategies aimed at European Union (EU) climate and energy policy, including its long-term vision of striving for EU climate neutrality by 2050, and regulatory mechanisms stimulating the achievement of such effects in the coming decades [28]. Achieving a reliable energy supply and environmental sustainability have become a global effort [29,30]. Achieving the EU's 2020 and 2030 climate and energy goals is key to a low-carbon energy transition, and this also applies to the transport sector, which is in the process of leading shifts in an attempt to alleviate the problems of climate change and air pollution [31].…”
Section: Introductionmentioning
confidence: 99%